Influence of Intellectual Capital Dimensions on Knowledge Process Capability and Organizational Performance - Barkat, Waseem; Beh, Loo See (Asian Network for Scientific Information, 2018)
Background and Objective: Intellectual Capital IC has been much studied in developed nations, but less considered on developing countries. This study was conducted in the context of a developing country like Pakistan to discover its impact on organizational performance. This study aimed to develop a conceptual model and to measure the individual dimensional effects of intellectual capital (human, structural, relational and technological capital) on knowledge process capability as well as organizational performance in the context of a developing country. Methodology: The survey was conducted with 267 respondents from the textile industry in Pakistan. This research used structural equation modeling with partial least squares regression. The structural equation modeling (SEM) is applied to run the multiple regression analysis and the analysis is performed with Warp partial least square (WarpPLS) software. Results: Results corroborate that all dimensions of intellectual capital have significant positive effects on organizational performance, except for structural capital. Similarly, knowledge process capability is partially mediated with relational, human and technological capital. Conclusion: This study presents implications for human resource managers and policy makers by examining the various dimensions of intellectual capital on organizational performance in the context of a developing country. This study offers selected relevant intellectual capital dimensions in workplace settings and suggests the importance of knowledge process capability in an organizational context.